Is relational aggression a means of pursuing social goals among adolescents with specific personality traits?. Issue 6 (18th April 2022) - Voulgaridou, Ioanna; Kokkinos, Constantinos M.; Markos, Angelos
Abstract: This study explored the short‐term longitudinal associations between Five Factor Model (FFM) and social goals (social dominance, popularity, and intimacy), with relational aggression (RAgg) as a mediator. RAgg was claimed to mediate the positive correlations of neuroticism with dominance and popularity, whereas extraversion was argued to positively relate to intimacy through low RAgg. The participants were 2207 Greek 13‐ to 16‐year‐olds ( M  = 14.04; 52.8% female), mostly from middle‐class families. Respondents completed three self‐report measures (T1, T2; 6‐month interval) during the school year. Confirmatory factor analysis explored a measurement model, whereas a longitudinal mediation model tested whether RAgg mediates the relationship between personality and social goals. Cross‐lagged correlations revealed associations of RAgg with neuroticism, dominance, and popularity but not openness, conscientiousness, extraversion, and agreeableness. Weak positive correlations emerged between FFM traits and intimacy, neuroticism, and dominance. Results indicated positive indirect effects from Τ1 neuroticism and negative from T1 agreeableness to Τ2 RAgg, which was then positively linked to T2 dominance and popularity. The research highlights the importance of RAgg as a mechanism for endorsing social goals for adolescents with specific personality traits. Intervention strategies aiming at limiting RAgg could consider agreeableness and neuroticism, providing adolescents with the behavioral tools to cope with anxiety and negative affect. Abstract : Personality, relational aggression and social goals. Highlights: Personality, social goals, and relational aggression were studied in adolescents. Short‐term longitudinal associations between constructs were examined. Relational aggression mediated the neuroticism to dominance and popularity pathway. Agreeableness was linked to dominance and popularity via relational aggression.